Violence in the school context and suicidal ideation in adolescence - Maria Aparecida Beserra; Sinara de Lima Souza; Marta Angélica Iossi Silva; Cláudia Alves de Sena; Cristina Maria Mendes Resende; Maria das Graças Carvalho Ferriani (Universidade Federal de Santa Maria, 2020)
Objective: to analyze the school violence suffered and practiced and its association with suicidal ideation among adolescents aged 12 to 18 years. Method: study conducted with 643 adolescents registered in state schools in the city of Recife, Pernambuco, Brazil. Two questionnaires were applied: "Global School-based Student Health Survey" and "Violence at School". For statistical analysis, the Chi-square test was used, degree of association was analyzed using the prevalence ratio. Results: the prevalence of school violence and suicidal ideation was 62.2% and 17.4%, respectively. About 28% of the adolescents reported having felt very sad, 14% of them reported feeling loneliness frequently. There was a significant association between suicidal ideation and violence in the age group of 15-18 years. Conclusion: the results point to the need for health actions aimed at strengthening the protective and prevention factors of risk situations for violence and suicidal ideation.